Impatience and uncertainty: experimental decisions predict adolescents' field behavior - Sutter, Matthias; Kocher, Martin; Glätzle-Rützler, Daniela; Trautmann, Stefan T. (CESifo working papers, 2011)
We study risk attitudes, ambiguity attitudes, and time preferences of 661 children and adolescents, aged ten to eighteen years, in an incentivized experiment and relate experimental choices to field behavior. Experimental measures of impatience are found to be significant predictors of health-related field behavior, saving decisions and conduct at school. In particular, more impatient children and adolescents are more likely to spend money on alcohol and cigarettes, have a higher body mass index, are less likely to save money and show worse conduct at school. Experimental measures for risk and ambiguity attitudes are only weak predictors of field behavior. -- experiments with children and adolescents ; risk ; ambiguity ; time preferences ; health status ; savings ; conduct at school ; external validity
Keywords: Arbeitspapier; Graue Literatur